Ataxin-2 Is Droppin' Some Knowledge. - Becker, L.A.; Gitler, A.D. (Neuron, 2018)
Ataxin-2 is an RNA-binding protein involved in translation regulation and mutated in neurodegenerative diseases, including ALS. In this issue of Neuron, Bakthavachalu et al. (2018) demonstrate that higher-order ataxin-2 RNA/protein assemblies are necessary for both translation-dependent learning and ALS-associated neurodegeneration in Drosophila.